Advances in Face Detection and Facial Image Analysis - Kawulok, Michal; Celebi, M. Emre.; Smolka, Bogdan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents the state-of-the-art in face detection and analysis. It outlines new research directions, including in particular psychology-based facial dynamics recognition, aimed at various applications such as behavior analysis, deception detection, and diagnosis of various psychological disorders. Topics of interest include face and facial landmark detection, face recognition, facial expression and emotion analysis, facial dynamics analysis, face classification, identification, and clustering, and gaze direction and head pose estimation, as well as applications of face analysis.
Introduction -- Face and Facial Landmark Detection -- Overview of Face Recognition Methods Gaze Direction and Head Pose Estimation -- Facial Emotions Recognition -- Facial Dynamics Analysis -- Deception Detection -- Face Liveness Detection -- Gender and Age Classification -- Applications of Automatic Face Analysis -- Conclusion.
Keywords: Engineering; Image processing; Engineering; Signal, Image and Speech Processing; Image Processing and Computer Vision; Electronic books